Respuesta :

Answer:

[tex]-72x^8[/tex]

Step-by-step explanation:

=> [tex](-2x^2)^3*(-3x)^2[/tex]

=> [tex]-8x^6*9x^2[/tex]

=> [tex](-8*9) *(x^6x^2)[/tex]

When bases are same powers are to be added

=> [tex](-72)(x^{6+2})[/tex]

=> [tex]-72x^8[/tex]

Answer:

[tex]- 72x^{8}[/tex]

Step-by-step explanation:

[tex]( - 2x^2 )^3 \times ( - 3x )^2[/tex]

Distribute the exponents to the brackets.

[tex]( - 2^3x^{2\times 3} ) \times ( - 3^2x^2 )[/tex]

[tex]( - 2^3x^{6} ) \times ( - 3^2x^2 )[/tex]

[tex]( - 8x^{6} ) \times ( 9x^2 )[/tex]

[tex]- 8 \times x^{6} \times 9 \times x^2[/tex]

[tex]- 8 \times 9 \times x^2 \times x^{6}[/tex]

Multiply like terms and add exponents with same bases.

[tex]- 72 \times x^{2+6}[/tex]

[tex]- 72 \times x^{8}[/tex]

ACCESS MORE